2021
DOI: 10.4049/jimmunol.2001031
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Abnormalities of Keratinocytes Initiate Skin Inflammation through the IL-23/T17 Axis in a MALT1-Dependent Manner

Abstract: Increasing evidence has supported the crucial role of CARD14 in the pathogenesis of psoriasis, whereas the precise cellular signaling involved in skin physiopathology remains poorly understood. In this article, we show that neither genetic ablation of Il17a nor elimination of T cells was sufficient to restrain the skin inflammation in a CARD14-E138A-mutation-induced psoriasis-like mouse model, whereas depletion of Il23, which extremely blocked the IL-23/T17 axis, was more effective. Targeting CBM complex by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…T-cell infiltration in active psoriatic skin creates a cytokine environment, mandating individual gene profiles in keratinocytes. This could overexpress various inflammatory mediators, enhancing local immune reactivity [ 48 , 49 ]. Moreover, better outcomes of trials addressing TNF-α inhibitors as a treatment in psoriasis patients reflect the critical role of this cytokine in the immunopathogenesis of psoriasis [ 50 , 51 ].…”
Section: Gut Microbiome Alterations In Psoriasismentioning
confidence: 99%
“…T-cell infiltration in active psoriatic skin creates a cytokine environment, mandating individual gene profiles in keratinocytes. This could overexpress various inflammatory mediators, enhancing local immune reactivity [ 48 , 49 ]. Moreover, better outcomes of trials addressing TNF-α inhibitors as a treatment in psoriasis patients reflect the critical role of this cytokine in the immunopathogenesis of psoriasis [ 50 , 51 ].…”
Section: Gut Microbiome Alterations In Psoriasismentioning
confidence: 99%
“…Our previous study revealed that E. coli could activate the inflammation-related NF-κB pathway. 23 In this study, AKT/NF-κB was significantly activated by E. coli induced infection, which might be closely associated with perpetuated inflammation. The subsequent results of this study demonstrated that E. colimediated NF-κB activation is regulated by AKT or MALT1.…”
Section: Discussionmentioning
confidence: 56%
“…46,47 Accumulating evidence supports the crucial role of MALT1 in the pathogenesis of inflammatory disorders. [46][47][48][49] Moreover, MALT1 inductively combines with other molecules to assemble the complicated CARD-BCL10-MALT1 (CBM) signalosome, which is involved in the nuclear translocation of NF-κB. 46,49,50 As the classical inflammatory pathway, NF-κB is activated by the degradation of IκBα, which is regulated by the phosphorylation of AKT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study identified that MALT1 was positively linked to inflammation (reflected by CRP, ESR, TNF‐α, IL‐1β, and IL‐17A) and disease activity (reflected by CDAI) in CD patients. Probable arguments would be that: (1) in terms of inflammation, MALT1 might stimulate the release of proinflammatory cytokines via activating B cell lymphoma/leukemia (BCL) 10, IL‐23/T17 axis, as well as NF‐κB and NLRP3 inflammasome 12,21,22 ; meanwhile, the formation of CARD11‐BCL10‐MALT1 complex played a key role in inflammation and immunity; thus, the dysregulated MALT1 might be linked with immunodeficiency or inflammation flare 23 ; therefore, a positive association was found between MALT1 and inflammation in CD patients. However, the linkage between MALT1 and IL‐6 was weakened.…”
Section: Discussionmentioning
confidence: 99%